A METHODOLOGICAL PROPOSAL FOR THE ENGLISH LANGUAGE - Neto Naciemento, Reginaldo (2007)
This article draws a methodological proposal for the English language teaching in the public high schools under a communicative, interdisciplinary, interactive and contextual approach. It begins with the theoretical base tracked by Chomsky (1996), Hymes (1991) and hold by the law 9495/96 LDB ( Law of Guideness and Bases for Education ). It portrays the difference between the terms learning and aquisition of a foreign language, and expose the main difficulties that envolve the pedagogical practice of English in Brazil and their possible causes for the obstructive resistence toward the second language learning. This study points to a pilot methodological proposal well suceeded for both teachers and students. This paper hints that exposition procedures of syntatic rules can be changed by funny communicative contents and or belonging to the student’s day-today reality which must exhalate, at first, those linguistic rules only inferentially developing the linguistic hability by mean of pleasing, contextualized and interdisciplinary strategies. This study ends granting some examples based on themes exctrated from day-to-day facts iconized in the lexicon and in its semantic extension. This is a descriptive study with a qualitative approach which has as main objective to generate favorable condictions for the effective aquisition and global interpretative performance to bring intellectual and social growth for students of English.